PERENCANAAN MANAJEMEN KONSTRUKSI PADA RUMAH SUSUN SEDERHANA SEWA 5 LANTAI KOTA PONTIANAK: PERENCANAAN MANAJEMEN KONSTRUKSI PADA RUMAH SUSUN SEDERHANA SEWA 5 LANTAI KOTA PONTIANAK - Ikbal, Muhamad; Anggara, Reghi; rosanti, indah; Helyanto, Helyanto (Jurusan Teknik Sipil Polnep, 2022)
The growth of the population with lower-middle incomes, both local residents and residents from outside theregion who are looking for job opportunities, increases, so that between the availability of housing and the factthat the income of the population does not match the impact and results in the lack of availability of affordableformal houses. To meet the housing needs for residents who have lower-middle income, the government has madeefforts with housing programs, one of which is the construction of simple rental flats (Rusunawa).The problem-solving method used in the discussion of construction management planning is in the form of a costmanagement system, at, human resources, construction work safety and quality, in Rusunawa construction work.Based on the results of the analysis of the methods carried out, it was found that the costs needed to complete thework on the construction of 5-story Simple Rental Flats on Jalan Tanjungpura, Pontianak City, amounted to Rp.54,801,530,000. In planning time, it took 115 weeks to complete the project work. In human resource planning,450 workers are needed for a more optimal project implementation. For planning the use of construction K3equipment, the things that are planned are in the form of planning the use of PPE and APK in accordance withthe type of work based on the Regulation of the Minister of Public Works number: 05/PRT/M/2014. For quality planning in the form of a list of quality specification tables and planning Work Plans and Requirements based onthe Regulation of the Minister of Public Works number: 04/PRT/M/2009